Extracellular Vesicles From Microalgae: Uptake Studies in Human Cells and Caenorhabditis elegans - Picciotto, Sabrina; Santonicola, Pamela; Paterna, Angela; Rao, Estella; Raccosta, Samuele; Romancino, Daniele Paolo; Noto, Rosina; Touzet, Nicolas; Manno, Mauro; Di Schiavi, Elia; Bongiovanni, Antonella; Adamo, Giorgia (Frontiers in Bioengineering and Biotechnology, 2022)
Extracellular vesicles (EVs) are lipid membrane nano-sized vesicles secreted by various cell types for intercellular communication, found in all kingdoms of life. Nanoalgosomes are a subtype of EVs derived from microalgae with a sustainable biotechnological potential. To explore the uptake, distribution and persistence of nanoalgosomes in cells and living organisms, we separated them from a culture of the chlorophyte Tetraselmis chuii cells by tangential flow filtration (TFF), labelled them with different lipophilic dyes and characterized their biophysical attributes. Then we studied the cellular uptake of labelled nanoalgosomes in human cells and in C. elegans, demonstrating that they enter the cells through an energy dependent mechanism and are localized in the cytoplasm of specific cells, where they persist for days. Our data confirm that nanoalgosomes are actively uptaken in vitro by human cells and in vivo by C. elegans cells, supporting their exploitation as potential nanocarriers of bioactive compounds for theranostic applications.